Actualization of Local Wisdom in Anticipating Radicalism of Religion In Gorontalo Indonesia - Rahmawati, Rahmawati; Rusli, Muh.; Yahiji, Kasim (KALAM, 2018)
This paper aims to express the values of local wisdom that belong to the people of Gorontalo, Indonesia. The values of local wisdom need to be explored to anticipate the symptoms of religious radicalism that began to emerge in the life of the people of Gorontalo city. Using phenomenology method, this study analyzes the data obtained through interviews, observation, documentation, and focus group discussions. The results of the study show that Gorontalo people have many local wisdom values, such as huyula; dulohupa;Modungohe ta Uda’a; Mopiyohu to bisala wawu huhutu; dan Tombulu. In the local wisdom found the value of mutual cooperation, deliberation, adherence to custom , tolerance, love for the motherland, moral education, self-purification, deepening of Islamic teachings, benevolence, and virtue. This study concludes that Gorontalo people have internal strength as social capital to anticipate the symptoms of religious radicalism.